The German minimum wage: Effects on business expectations, profitability, and investments - Mario Bossler; Nicole Gürtzgen; Benjamin Lochner; Ute Betzl; Lisa Feist (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2018)
In this article, we analyze the effects of the introduction of the German minimum wage using difference-in-differences estimations applied to the IAB Establishment Panel. The treatment effects on the treated establishments show a slight reduction in the employers' expected development of business volume. When we analyze the effects of the minimum wage on the net sales of intermediates and wages costs, we observe a reduction, which is fully explained by the increase in wage costs induced by the minimum wage. The results do not point to effects on establishment-level productivity or capital investments. Looking at investments in human capital, we do not observe any effects on apprenticeship offers or the placement of apprentices. If anything, the results point at a slight reduction in the provision of further training.
Keywords: C23; J38; 330; Minimum Wage; Business Expectations; Profitability; Training